The Effects Of Selenium And Tocotrienol Supplementation On The Muscle Contractile Properties, Fatigue, Emg And Antioxidant Status Of Gastrocnemius Muscle Of Trained And Untrained Rats - Alwan, Mohand R. (2009)

(untitled)
Exercise induces radical-mediated oxidative damage of skeletal muscle membranes which has been implicated in the fatigue process. Selenium (S) is an important component of cellular selenocompounds and is an integral component of glutathione Peroxidase (GPx), which catalyze the reduction of harmful peroxides. Tocotrienol (T) is a major chain breaking antioxidant that has been shown to reduce contraction mediated oxidative damage. We hypothesized that S and T supplementation would positively affect muscle contractile function and increase antioxidant enzymes activities during exercise. To test this postulate, were used sixty-four male Wistar-Kyoto rats at weight between 300-350g randomized into eight groups with eight rats per group rats these sample size was calculated using PS software based on comparing two means of superoxide dismutase (SOD).